2017
DOI: 10.13075/mp.5893.00605
|View full text |Cite
|
Sign up to set email alerts
|

Personal and occupational risk factors for carpal tunnel syndrome in meat processing industry workers in Northern Italy

Abstract: Background: Carpal tunnel syndrome (CTS) is a musculoskeletal condition that often impairs the fitness to work. Our aim is to retrospectively evaluate the association between physical exposures in meat processing industry in Northern Italy and the CTS, taking into account non-occupational factors. Material and Methods: A cross-sectional study was performed to include 434 workers (236 males, 198 females, 37.0±10.6 years old, working age: 12.6±10.8 years) from meat processing industries. Signs and symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 57 publications
(128 reference statements)
3
39
0
6
Order By: Relevance
“…Compared with previous longitudinal studies, we found a stronger correlation with smoking and CTS . Work‐related factors, such as significant exposure to vibration and some specific occupations, may be associated with a high prevalence of CTS, but the problem is still debated . In our cohort, farmers and manual workers were at increased risk for CTS compared with clerical workers and entrepreneurs, as expected based on previously published literature …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared with previous longitudinal studies, we found a stronger correlation with smoking and CTS . Work‐related factors, such as significant exposure to vibration and some specific occupations, may be associated with a high prevalence of CTS, but the problem is still debated . In our cohort, farmers and manual workers were at increased risk for CTS compared with clerical workers and entrepreneurs, as expected based on previously published literature …”
Section: Discussionsupporting
confidence: 93%
“…[11][12][13][14] Work-related factors, such as significant exposure to vibration and some specific occupations, may be associated with a high prevalence of CTS, but the problem is still debated. 6,8,17 In our cohort, farmers and manual workers were at increased risk for CTS compared with clerical workers and entrepreneurs, as expected based on previously published literature. 28,29,34 Among women, overweight/obesity was associated with CTS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…uma prevalência de 7,8% na população trabalhadora, de modo que, dependendo da atividade a ser exercida, esta estimativa pode chegar a 20% 10,11 .…”
unclassified
“…Ocorre entre os 40 e 60 anos, sendo que afeta mais as mulheres. Estudos transversais sobre STC evidenciam prevalência de 9,2% no sexo feminino e 0,6% no sexo masculino 3,8,9,11,13,[15][16][17][21][22][23] .…”
unclassified